Natural variation of chronological aging in the Saccharomyces cerevisiae species reveals diet-dependent mechanisms of life span control. (December 2018) - Jung, Paul; Zhang, Zhi; Paczia, Nicole; Jaeger, Christian; Ignac, Tomasz; May, Patrick; Linster, Carole
Abstract Aging is a complex trait of broad scientific interest, especially because of its intrinsic link with common human diseases. Pioneering work on aging-related mechanisms has been made inSaccharomyces cerevisiae, mainly through the use of deletion collections isogenic to the S288c reference strain. In this study, using a recently published high-throughput approach, we quantified chronological life span (CLS) within a collection of 58 natural strains across seven different conditions. We observed a broad aging variability suggesting the implication of diverse genetic and environmental factors in chronological aging control. Two major Quantitative Trait Loci (QTLs) were identified within a biparental population obtained by crossing two natural isolates with contrasting aging behavior. Detection of these QTLs was dependent upon the nature and concentration of the carbon sources available for growth. In the first QTL, theRIM15 gene was identified as major regulator of aging under low glucose condition, lending further support to the importance of nutrient-sensing pathways in longevity control under calorie restriction. In the second QTL, we could show that theSER1 gene, encoding a conserved aminotransferase of the serine synthesis pathway not previously linked to aging, is causally associated with CLS regulation, especially under high glucose condition. These findings hint toward a new mechanism of life span control involving a trade-off between serine synthesis and aging, most likely through modulation of acetate and trehalose metabolism. More generally it shows that genetic linkage studies across natural strains represent a promising strategy to further unravel the molecular basis of aging. A metabolic block favoring long sweet life A Sake yeast strain deficient in producing the protein building block serine lives longer than other yeast strains, especially when exposed to high glucose. A team led by Carole Linster at the University of Luxembourg found a broad variability of lifespan when analyzing more than fiftySaccharomyces cerevisiae strains isolated from around the world. Combining hundreds of lifespan measurements with genotype data from a progeny obtained by crossing the long-lived Sake strain and a short-lived collection strain, they identified two genes playing a pivotal role in causing the contrasting aging behavior of the parents:RIM15, when glucose was limiting andSER1, when glucose was plenty.RIM15 is part of a signaling cascade also regulating aging in mammals;SER1 revealed that a blockage in serine synthesis reprograms metabolism to favor glucose storage and long life.